They Raised Me Up : A Black Single Mother and the Women Who Inspired Her - Wilkins, Carolyn (Carolyn Marie) (Book collections on Project MUSE., 2013)
At the height of the cocaine-fueled 1980s, Carolyn Wilkins left a disastrous marriage in Seattle and, hoping to make it in the music business, moved with her four-year-old daughter to a gritty working-class town on the edge of Boston. They Raised Me Up is the story of her battle to succeed in the world of jam sessions and jazz clubs--a man's world where women were seen as either sex objects or doormats. To survive, she had to find a way to pay the bills, overcome a crippling case of stage fright, fend off a series of unsuitable men, and most important, find a reliable babysitter.